PENGARUH MODEL DELON AND MCLEAN TERHADAP KEPUASAN PENGGUNA PADA PENGGUNA APLIKASI OVO DI SURABAYA - Denis Fidita Karya; Amilia Nur Indah Saputri (Universitas Nahdlatul Ulama Surabaya, 2020)
This study aims to determine whether there is a significant influence on the variables of information quality, service quality, system quality, users, and net benefits on user satisfaction (a study on users of the OVO application in the city of Surabaya). The method in this study uses a questionnaire in the form of a questionnaire and is distributed based on the research objectives. Respondents taken in this study were 115 respondents. Using a non-probability sampling method with a purposive sampling approach, for the method used to analyze the data in the study using SmartPLS 3.0. Based on the data analysis that has been done, it is found that the quality of information has no significant effect on user satisfaction. Service quality has a significant effect on user satisfaction. System quality has no significant effect on user satisfaction, while users have a significant effect on user satisfaction and finally, net benefits have a significant effect on user satisfaction.